Feasibility of a Single Common Powertrain Lubricant: Hydraulic System Investigations at Low Temperatures - Wendel, Glenn; Montemayor, Alan F; Frame, Edwin A; Comfort, Allen S (2011)
This project was conducted in support of the feasibility study for the U.S. Army Single Common Powertrain Lubricant (SCPL). U.S. Army vehicles were surveyed to determine the types of hydraulic system pumps that are used. The hydraulic system from a representative vehicle (6K) Rough Terrain Fork Lift was selected as the basis for a bench test apparatus that was used to investigate the low temperature flow performance of various fluids. The test rig was assembled and low temperature tests were conducted. Results indicated that a commercially available dedicated hydraulic fluid had outstanding low temperature flow performance. Given the observed low temperature flow performance of the current fielded Arctic Engine Oil, MIL-PRF-46167D, it is recommended that the proposed SCPL should have equivalent or lower viscosity at low temperatures. The original document contains color images.